ArcGIS Pro 2.x cookbook : create, manage, and share geographic maps, data, and analytical models using ArcGIS Pro - Corbin, Tripp; Malhoski, Ryan (Packt Publishing, 2018)
ArcGIS Pro makes use of the modern ribbon interface and 64-bit processing to increase the speed and efficiency of using GIS. If you want to gain a thorough understanding of the various data formats that can be used in ArcGIS Pro and shared via ArcGIS Online, then this book is for you.